2015
DOI: 10.1007/s00520-015-2891-6
|View full text |Cite
|
Sign up to set email alerts
|

Leveraging iPads to introduce meditation and reduce distress among cancer patients undergoing chemotherapy: a promising approach

Abstract: The use of iPads during chemotherapy is a potentially effective way to introduce meditation as a stress management tool for people with cancer.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 9 publications
1
2
0
Order By: Relevance
“…The efficacy of acupressure in relieving chemotherapy-induced stress and anxiety, as shown in this study, is consistent with findings in previous studies, which showed that different forms of acupressure significantly reduced pretreatment anxiety and chemotherapy-induced nausea [24,25]. A previous QI study found that providing patients with guided meditation delivered through iPads decreased average distress levels by 46% ( P <.01) in patients undergoing chemotherapy [26]. Another clinical trial also found that mindfulness interventions significantly lowered blood pressure, heart rate, oxygen saturation, and perceived stress in women undergoing breast biopsies [27].…”
Section: Discussionsupporting
confidence: 91%
“…The efficacy of acupressure in relieving chemotherapy-induced stress and anxiety, as shown in this study, is consistent with findings in previous studies, which showed that different forms of acupressure significantly reduced pretreatment anxiety and chemotherapy-induced nausea [24,25]. A previous QI study found that providing patients with guided meditation delivered through iPads decreased average distress levels by 46% ( P <.01) in patients undergoing chemotherapy [26]. Another clinical trial also found that mindfulness interventions significantly lowered blood pressure, heart rate, oxygen saturation, and perceived stress in women undergoing breast biopsies [27].…”
Section: Discussionsupporting
confidence: 91%
“…Millegan et al. reported that the use of iPads during chemotherapy is a potentially effective way to introduce meditation as a stress management tool for people with cancer [ 20 ]. Therefore, it is recommended to provide distress management services to cancer patients as soon as possible, especially to provide evidence-based practice for distress management.…”
Section: Discussionmentioning
confidence: 99%
“…Introduce some form of mindfulness meditation into the daily routine. Mindfulness practices have been shown to increase empathy (Chanler, 2017; Danucalov et al, 2017; Koszycki et al, 2016; Laneri et al, 2017; Leppma and Young, 2014), enhance focus and concentration (Basso et al, 2018; Zanesco et al, 2016), reduce stress and anxiety (Barrett, 2017; Basso et al, 2018; Millegan et al, 2015; Victorson et al, 2017; Waelde et al, 2017), foster creativity (Muller et al, 2016) and mitigate burnout (Bostock et al, 2018; Charoensukmongkol, 2013; Heeter et al, 2017; Schnaider-Levi et al, 2017). Additionally, work done by Moniz et al (2016) explicitly demonstrates how mindfulness and meditation practices can directly impact librarians and user experience within multiple service areas.…”
Section: Conclusion: Developing a Librarian Sādhanāmentioning
confidence: 99%